Rapid response teams—how and who? A protocol for a randomised clinical trial evaluating the composition of the efferent limb of the rapid response system. Issue 3 (27th December 2021) - Føns‐Sønderskov, Morten B.; Subbe, Chris; Kodal, Anne Marie; Bunkenborg, Gitte; Bestle, Morten H.
Abstract: Background: Many patients experiencing deterioration have documented deviation of vital signs prior to the deterioration event. Increasing focus on these patients led to the rapid response systems and their configuration with afferent and efferent limbs. The two most prevalent team constellations in the efferent limb are the medical emergency team (MET), usually led by a doctor, and the critical care outreach team (CCOT), usually led by a nurse. The two constellations have not previously been examined in a comparative clinical trial. Methods: This is a single centre non‐inferiority randomised controlled trial of MET vs CCOT. All patients will be randomised at the time of the call. The intervention group will be the critical care outreach team. The primary outcome is mortality at 30 days and the occurrence of serious adverse events. All patients will be followed for 90 days. We aim to detect or reject a change of 7% in mortality whilst accepting a type I error of 5 and type II error of 20, using a sample size of maximum of 2000 individual patients. Discussion: There is evidence supporting a benefit for the patient when using rapid response systems; however, earlier randomised studies are marked by cross‐contamination and selection bias. Previous studies have primarily examined the effect of RRS on hospital cardiac arrests (IHCA) and mortality. Our study will be examining the effect on intensive care unit admissions as well as the ICHA and mortality. Conclusion: This study may highlight potential benefits of specific configurations of rapid response systems and their impact on safety outcomes.